From Hadrianic Persecution to Living Tradition: The Divergent Afterlives of the Trajan–Gregory and Eustace–Placidus Legends in the Legenda Aurea, Dante, and the Basilica di Sant’Eustachio in Rome - Meledandri, Giovanni (Advances in Social Sciences Research Journal, 2026)
The early second century CE offers limited contemporary evidence for Christian persecution and martyrdom, centered on the Pliny–Trajan correspondence. The narratives in the Legenda Aurea (c. 1260), populated this era with vivid chronicles. This article compares two such stories set in the Trajan/Hadrian period: the legend of Emperor Trajan’s posthumous salvation through Pope Gregory the Great’s intercession, and the romance of Placidus/Eustace, his wife Theopista, and sons, who convert via a stag vision, endure trials, and suffer martyrdom in a brazen bull. While both exemplify hagiographic romance, they serve divergent functions—one enabling theological speculation on divine mercy and the salvation of virtuous pagans, the other modeling lay endurance and family fidelity. Dante Alighieri incorporates the Trajan legend prominently in Purgatorio X and Paradiso XX to dramatize God’s inscrutable justice and the providential role of empire but omits Eustace entirely. Reception history reveals a contrasting afterlife: Trajan’s story fuels high theology, while Eustace’s sustains a living cult at Rome’s Basilica di Sant’ Eustachio, where iconography, statuary, and local tradition persist despite the 1969 removal of the feast from the General Roman Calendar. Drawing on source criticism, Dante commentary, Bollandist hagiography, and unpublished contemporary visuals and material evidence, this study illuminates how medieval legends bridged historical gaps and how critical scholarship and devotional practice continue to coexist in Catholic tradition.